Effect of memory on the contemporary architectural design concept - Muhammad Abdulnaser Ahmed Abdulzaher; Tang Jian; Maged Youssef (Ain Shams Engineering Journal, 2023)
The human memory is the mental storehouse that preserves the events, facts, and dreams that happen to him in his life or his mind creates them. According to psychologists and sociologists, the memory pursued by human beings is linked to the mine of creativity as it generates special human emotions. Architects embodied the Double Code Theory through the content of their personal memories. They presented architectural formations that carried two meanings: the first is visible to the audience, and the other is hidden and related to the memory of the architect, where the architect relied on recalling events related to his memory. Architects recall their memories and work to recall their own memories and are inspired by their designs, as the architectural buildings become of historical, civilizational, and cultural value. Thus, the scope of this research belongs to the field of diaries of architecture, trying to unveil the secrets and intentions of architects who inspire their design concepts from the memory of civilizations and their own memories. This paper exposes the ideas of the most prominent designers who worked on buildings around the world, whereas the main aim of this paper is to re-read and interpret contemporary architectural languages that rely on memory in their design concepts to enable us to deconstruct and understand them from the perspective of memories of the past and to understand the intended message beyond, depending on methods of analysis by tracing particles, definitions, and theories through presenting a literature review to highlight what came in the precedent research in this topic. This research hypothesizes that the memory is the inspiration source for contemporary architecture. Throughout the paper, the analytical method investigates this hypothesis using certain parameters of analysis on three case studies, followed by a comparison to explore how each architect of these projects inspired his own memory to lead the design setting. One of the most prominent findings is the process of comprehending the design concept can’t be easy for visitors unless they make an intellectual and physical effort to disclose the secret of architect and truly detect the inspirational memory. Another important finding is that the memory of architect, implemented in the design ideas, always touches whether religious or political events or personal experiences.